2011
DOI: 10.4103/2152-7806.82084
|View full text |Cite
|
Sign up to set email alerts
|

Trigeminal ganglion neuron density and regulation of anterior choroid artery vasospasm: In a rabbit model of subarachnoid hemorrhage

Abstract: Background:Subarachnoid hemorrhage (SAH) is associated with severe vasospasm caused by a variety of neurochemical mechanisms. The anterior choroid arteries (AChAs) are innervated by vasodilated fibers of the trigeminal ganglion (TGG). The goal of this study was to determine whether there is a relationship between the neuron density of the TGG and the severity of AChAs vasospasm with SAH.Methods:Thirty-two rabbits were used for the study; eight served as the baseline control group, seven as a SHAM group, with i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…The exact mechanism of how activation of the trigeminal nerve causes cerebral vasodilation is not fully understood, but there is evidence that the effect is primarily mediated by postganglionic trigeminal fibers, principally V1 branches 44 , 45 . In animal studies, it has been shown that postganglionic trigeminal fibers play a role in attenuating vasospasm after SAH, and that lower density of V1 fibers in the vasculature have been associated with increased incidence of spasm, which is highly suggestive of the trigeminal nerve having tonic control of cerebral vessel diameter 46 48 . These fibers contain calcitonin gene-related peptide (CGRP) and Substance P at their synaptic terminals, and when stimulated, these potent vasodilatory substances are released, resulting in vasodilation 41 , 49 , 50 .…”
Section: Discussionmentioning
confidence: 99%
“…The exact mechanism of how activation of the trigeminal nerve causes cerebral vasodilation is not fully understood, but there is evidence that the effect is primarily mediated by postganglionic trigeminal fibers, principally V1 branches 44 , 45 . In animal studies, it has been shown that postganglionic trigeminal fibers play a role in attenuating vasospasm after SAH, and that lower density of V1 fibers in the vasculature have been associated with increased incidence of spasm, which is highly suggestive of the trigeminal nerve having tonic control of cerebral vessel diameter 46 48 . These fibers contain calcitonin gene-related peptide (CGRP) and Substance P at their synaptic terminals, and when stimulated, these potent vasodilatory substances are released, resulting in vasodilation 41 , 49 , 50 .…”
Section: Discussionmentioning
confidence: 99%
“…For trigeminal network, injuries lead to increased intraocular pressure, 27 scalp ischemia and hair loss, 28 hypoacusia, 29 decreased cerebral blood flow due to anterior choroidal artery vasospasm following subarachnoid hemorrhage. 30 Trigeminal ganglion dysfunctions cause increased intracranial temperature, increased intracranial–intraocular pressure, and acid–base balance disturbances. Figure 2 shows the histological appearances of the trigeminal ganglion on the sphenoid bone.…”
Section: Introductionmentioning
confidence: 99%